UPGRADING THE FRIDAY SERMON AS AN EDUCATIONAL ELEMENT OF UNITY IN A MULTI-FAITH NATION - MOHD RASDI, MOHD TAJUDDIN (Human Sustainability Procedia, 2018)
The Friday Sermon in Malaysia is prepared by the various departments of religious affairs in each state of Malaysia. The main purpose of the Friday sermons is to educate the general public about values of Islam and its relevance to modern life and nation building. An examination of 100 Friday Sermons was analysed from the JAIS website (Jabatan Agama Islam Selangor or Selangor Religious Affairs Department). The sermons were examined from three aspects of unity building; firstly the sermons were scrutinised for any phrases insulting other faiths, secondly the sermons were examined whether it deals with issues of extremism in a significantly serious manner, and thirdly, the sermons were examined whether it contains discussion of shared values with other faiths. Firstly, It was found that the sermons had never contained phrases insulting other faiths. Secondly, it was found that the sermons dealt very little on issues of extremism in and outside of Malaysia. Thirdly, the sermons never contained any discussion of shared values between faiths. The implications of the finding shows that the sermons have been drafted in a way that isolates the Muslim community from caring about other faiths in relation to extremist issues as well as shared values. If this method of writing continues Muslims in such country like Malaysia would fail to appreciate theidea of nation building because they would only care about the development and sustainability of their own faith.